Black liquor gasification combined cycle with CO2 capture-Technical and economic analysis - Ferreira, Elzimar Tadeu de Freitas [UNESP]; Balestieri, José Antonio Perrella [UNESP] (Elsevier B.V., 2015)
The pulp and paper sector is intensive in the use of energy, and presents a high participation in the industrial context, specially based in the black liquor, a renewable source generated in the pulp process. Black liquor gasification is not still completely dominated; however, it has the potential of becoming an important alternative for the pulp and paper sector. In this article, the traditional steam cycle based on chemical recovery and biomass boilers associated to backpressure/extraction turbine is compared to black liquor gasification combined cycle schemes, associated to biomass boiler, considering the technical and economic attractiveness of capturing and sequestering CO2. Results show that despite its interesting exergetic efficiency, the adoption CO2 capture system for BLGCC did not prove to be attractive under the prescribed conditions without major incentive.
Keywords: Cogeneration; Black liquor gasification; Combined cycle; Exergetic analysis; CO2 capture